Informal contracting between and within firms (Revista de Administração, 2017)
While informal contracts are widely used in modern economies, limited systematic empirical evidence is available to researchers and policy makers. This paper aims to fill the gap by discussing a selected sample of empirical works through the lens of a theoretical framework that clarifies the role of informal contracts. We also highlight unexplored research opportunities offered by more recent theoretical models that investigate how informal contracts are built over time, how they are subject to path dependency, and how relational rents are created, and are awaiting empirical analysis.